Teaching International Students in a Difficult Time: The Importance of Empathy - Tavares, Vander (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
The coronavirus (COVID-19) pandemic has forced instructors and students to work together under constantly evolving circumstances. The abrupt transition to online education has contributed to making the educational experiences of instructors and students more emotionally complex and intense. Growing attention has been directed toward understanding the challenges international students face and their impact on the students’ learning experiences, considering the unprecedented difficulties the global pandemic has posed for international student mobility. In this context, instructors are in a unique position to support international students. One way to do so is by being (more) empathetic. Empathy is important because it not only helps us feel for and with the other, but also improves the academic outcomes of students. This paper discusses the importance of empathy in teaching international students by expanding on the concept of teacher empathy. This paper also critically examines the experiences of international students in higher education in several domains of lived experience, such as the linguistic, academic, social, cultural, and psychological. Other aspects of empathy presented are its contagious nature and the concept of radical empathy. This paper concludes by highlighting the practical application of empathy in light of international students’ experiences.